POSSIBILITIES OF REGULATION OF COMPOSITION AND CHARACTERISTICS OF MOLDING SANDS IN CASTING HOUSES - A. P. Melnikov; D. M. Golub; V. M. Karpenko; E. V. Filipenko (Литьë и металлургия)
The influence of microalloying and modifying elements on structure and characteristics of pearlitic bearing cast irons with vermicular graphite was investigated.